Watching (natural) beauty boosts task performance: testing the nature-as-reward hypothesis - Joye, Yannick; Lange, Florian; Lisauskienė, Asta; Makauskaitė, Diana (Psychological research, 2024)
In two online studies, we tested the “nature-as-reward hypothesis”, which suggests that superior cognitive task performance following nature exposure reflects a general performance improvement, driven by the reward value of beautiful things. In both between-subjects experiments, participants viewed either beautiful or less beautiful images for 10 s, comprising beautiful mountain photos (vs. less beautiful mountain drawings) in Study 1 and beautiful fractals (vs. less beautiful pixelated images) in Study 2. Following image exposure, participants engaged in a ticking task requiring them to freely tick up to 200 boxes. Participants had to complete four (Study 1) or five (Study 2) of such ticking tasks, with each task being preceded by either a beautiful or less beautiful image. In Study 1, for a subset of participants the ticking task was framed as a game. We found that in Study 1, ticking declined over the ticking rounds when participants had viewed less beautiful line drawings of mountains, while ticking performance remained unchanged over the rounds after seeing beautiful mountain images. However, when the ticking task was framed as a game, there was no significant difference in ticking performance between the two beauty conditions over the four ticking rounds. In Study 2, participants ticked more boxes over all ticking rounds after viewing images of beautiful fractals compared to less beautiful pixelated images. In line with the nature-as-reward hypothesis, these findings show that brief exposures to beautiful (nature) images can motivate to work and that framing tasks as a game can attenuate this beauty advantage.